Peter Konwitschny, Opera and Theatre Director Shaping the Profile of the Bratislava Opera of a New Millennium - Mojžišová Michaela (Slovenské divadlo)
The paper examines the work of the acclaimed German opera and theatre director Peter Konwitschny at the Opera of the Slovak National Theatre. The authoress bases herself on an analysis of the productions of Eugen Onegin (2005) [Eugene Onegin], by Tchaikovsky, Puccini’s Madama Butterfly (2007) and Bohéma (2013) [La bohème], Janáček‘s Vec Makropulos (2015) [The Makropulos Affair], and Halévy‘s Židovka (2017) [La Juive], all of which, save for Janáček‘s opera, the Opera of the Slovak National Theatre has borrowed from foreign theatre scenes. The authoress makes a stocklist of the basic principles of Konwitschny’s direction signature and his contribution to theatre production, as well as to the artistic ensemble of the Bratislava Opera.